Long-Term Outcomes After Stent Insertion in Patients with Early and Late Hepatic Vein Outflow Obstruction after Living Donor Liver Transplantation. (July 2018) - Kim, Kyeong Sik; Lee, Ji soo; Choi, Gyu Sung; Kwon, Choon Hyuck David; Cho, Jae-Won; Lee, Suk-Koo; Kim, Jong Man
Abstract : Abstract: The purpose of this study was to describe the long-term effects of stent insertion in patients with hepatic venous outflow obstruction who underwent living donor liver transplantation (LDLT). Between January 2000 and December 2009, 622 adult patients underwent LDLT at our hospital. Of these patients, 21 (3.3%) were diagnosed with hepatic venous outflow obstruction (HVOO). Among these patients, stent insertion was performed in 17 patients. Then, the patients were divided into "early" and "late" groups according to when they received their HVOO diagnoses. The median follow-up period was 54.2 months (range, 0.5-192.4 months). Stent insertion was successful in 8 of 10 patients in the early group and 6 of 7 in the late group, and the 5-year primary patency rates were 46% and 20%, respectively. In both groups, patients with recurrent HVOO at the beginning had kinking confirmed by venography, and patients who had their stents for more than 3 years maintained long-term patency. Stent insertion is feasible in the long term in LDLT patients if patency is maintained. However, if kinking is seen on venography, patency maintenance is difficult. Therefore, to improve patency rate, initial surgical repair should be considered or a new indication might be needed. Figure. No caption available.